1993
DOI: 10.1172/jci116225
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor stimulates amino acid transport in plasma membrane vesicles from rat liver.

Abstract: Severe infection is characterized by a translocation of amino acids from the periphery to the liver, an event that is mediated in part by cytokines such as tumor necrosis factor-a (TNF). We investigated the activities of Na '-dependent transport systems A, ASC, and N in hepatic plasma membrane vesicles (HPMVs) prepared from rats treated with TNF in vivo. TNF did not alter sodium uptake but resulted in time-and dose-dependent fivefold and 50% maximal increases in system A and system N activity, respectively, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 33 publications
(48 reference statements)
1
15
0
Order By: Relevance
“…TNF-α has been shown to exhibit a permissive effect in enhancing the stimulation of amino acid transport by glucagon [34]. The marked increase in Na + -dependent amino acid transport by TNF-α in i o is, in part, mediated by glucocorticoids [35]. Alanine transport in hepatic membrane vesicles has also been reported to be stimulated in endotoxin-treated rats [36].…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α has been shown to exhibit a permissive effect in enhancing the stimulation of amino acid transport by glucagon [34]. The marked increase in Na + -dependent amino acid transport by TNF-α in i o is, in part, mediated by glucocorticoids [35]. Alanine transport in hepatic membrane vesicles has also been reported to be stimulated in endotoxin-treated rats [36].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with TNF-α has also been shown not to produce any effect on the activity of ecto-ATPase (Pacitti et al 1993). Moreover, it has recently been demonstrated that Spgp, rather than ectoATPase, is the major driving force of bile salt transport across the canalicular membrane (Gerloff et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Since there was evidence for an increase in alveolar epithelial liquid clearance, the second objective was to study the mechanism by administering amiloride, a sodium transport inhibitor, and propranolol, a beta-adrenergic antagonist, into the distal airspaces of the rats with pneumonia. Although TNF ␣ has been reported to play a role in increased lung epithelial permeability in acute lung injury (13), TNF ␣ has also been reported to increase sodium-dependent amino acid transport in rat hepatocytes (14). Therefore, our third objective was to test the hypothesis that TNF ␣ mediates the bacterially induced increase in alveolar fluid clearance.…”
Section: Introductionmentioning
confidence: 99%
“…Some experimental studies implicate TNF␣ in the increase of lung endothelial or epithelial permeability (13,48). However, it is also known that TNF␣ can increase sodium-dependent amino acid transport in rat hepatocytes (14). Therefore, our third objective was to test the hypothesis that TNF␣ could mediate the increase in alveolar fluid clearance in this 24-h model of severe bacterial pneumonia.…”
mentioning
confidence: 99%